2019
DOI: 10.1590/2447-536x.v25i4.2018
|View full text |Cite
|
Sign up to set email alerts
|

Soil management in integrated rose production system

Abstract: Integrated production systems have been used with various crops, and their use in floriculture is innovative. The effects of green fertilization in floriculture and the appropriate fertilization levels are still unknown. The aim was to identify the best dose of chemical fertilizer, with or without green fertilization, for integrated production of ‘Carola’ roses. The treatments consisted of 4 doses of the chemical fertilization recommended for rose bushes, (25%, 50%, 75%, and 100%), with or without green fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(19 reference statements)
0
5
0
1
Order By: Relevance
“…In this context, rose plants maintained strong growth under adequate levels of nutrient elements [ 40 ]. Similarly, the growth attributes of rose plants were enhanced when the plants received proper levels of N, P, and K elements [ 67 , 68 ]. Furthermore, the P detected in GE is essential for root development promotion and, consequently, increased the water and nutrient absorption capability [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, rose plants maintained strong growth under adequate levels of nutrient elements [ 40 ]. Similarly, the growth attributes of rose plants were enhanced when the plants received proper levels of N, P, and K elements [ 67 , 68 ]. Furthermore, the P detected in GE is essential for root development promotion and, consequently, increased the water and nutrient absorption capability [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…They contribute to soil fertility, decomposing organic matter, degrading pollutants, and facilitate nutrient cycling [41]. However, continuous rose cropping can have detrimental effects on soil microbial abundance and community structure, leading to an imbalance where fungal dominance surpasses bacterial dominance [9]. To address these issues, previous studies have explored the use of microbes to improve soils affected by continuous cropping.…”
Section: Exploring Variations In Bacterial Communities Across Differe...mentioning
confidence: 99%
“…Commonly known as edible roses, Rosa rugosa (Rosales: Rosaceae) is a significant cash crop cultivated using facility cultivation techniques, which have improved the growing conditions of the crop, while also introducing certain challenges [9]. Continuous monocropping of the same crop can disrupt the soil nutrient balance, leading to the depletion of specific nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Or that fertilizer is a substance added to soil or sprayed on vegetative system of plant to improve its growth and increase its productivity, compound fertilizers that contain major elements such as nitrogen, phosphorus and potassium, which are important for growth and plants development, using a balanced proportion of NPK compound fertilizer [6]. Several studies have been conducted to determine effect of NPK fertilizers in growth and flowering in ornamental plants, [7] found in an experiment on Rose bushes Carola cultivar, in a study that included adding chemical fertilizer NPK at four levels (25, 50, 75, and 100%) and comparing it with organic fertilization, addition of chemical fertilizers outperformed organic ones in flowering stems number, plant dry weight, and content of flowering stems of macro and microelements, especially at level of 100%. [8] Conducted an experiment aimed to improve flower productivity and concentration of N,P,K elements in nutrient solution, and foliar application of plant growth promoters (PGP) on Rosa Damascene and found that NPK fertilizer significantly increased in leaf nitrogen phosphor and potassium content.…”
Section: Introductionmentioning
confidence: 99%